2020
DOI: 10.1186/s10020-019-0130-1
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of miR-21 and miR-150 is a feature of anti-mitochondrial antibody-negative primary biliary cholangitis

Abstract: Background & Aims: Anti-mitochondrial-autoantibodies (AMA) remain a hallmark of Primary Biliary Cholangitis (PBC) however approximately 10% of patients test negative for these antibodies. They do not differ in terms of biochemistry or clinical presentation from AMA positive ones. Epigenetics play a key role in immune signalling. Two microRNAs (miRs), namely, miR-21 and miR-150 are known to be involved in liver inflammation and fibrosis. The expression of those two microRNAs and their downstream targets were an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…miR-21 was previously implicated in the development of fibrosis; however, in this study, a small increase was observed in the early stages of PBC (F0-F2), followed by a substantial increase in cirrhotic PBC. There was no correlation between the levels of miR-21 and the stages of fibrosis, which is in agreement with previous reports [ 49 , 50 ]. Even though miR-21 ablation has been shown to protect from fibrosis and acute oxidative stress in the livers of mice with bile duct ligation, it was an acute model of cholestasis, which did not completely mimic the sustained cholestasis that occurs in PBC [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…miR-21 was previously implicated in the development of fibrosis; however, in this study, a small increase was observed in the early stages of PBC (F0-F2), followed by a substantial increase in cirrhotic PBC. There was no correlation between the levels of miR-21 and the stages of fibrosis, which is in agreement with previous reports [ 49 , 50 ]. Even though miR-21 ablation has been shown to protect from fibrosis and acute oxidative stress in the livers of mice with bile duct ligation, it was an acute model of cholestasis, which did not completely mimic the sustained cholestasis that occurs in PBC [ 51 ].…”
Section: Discussionsupporting
confidence: 93%
“…For the regulation of RasGRP1, it is known that signal termination can be mediated by DGKα and DGKζ via the conversion of DAG to PA. For the activation, RasGRP1 can be phosphorylated at T184 by PKCα. Other less-well characterized mechanisms include HSP90- [ 46 ] and miR-21-mediated degradation [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the degradation of RasGRP1 can be mediated by HSP90 acetylation [ 46 ]. There is emerging evidence that microRNAs also play a role in the RasGRP1 expression; specifically, miR-21 was shown to suppress the expression of RasGRP1 [ 47 , 48 ]. Conversely, the downregulation of miR-21 increased the RasGRP1 expression in vitro [ 49 ].…”
Section: Ras Guanine Nucleotide-releasing Protein 1: Regulationmentioning
confidence: 99%
“…In the present review, some functional ncRNAs are listed in Table 1, mainly including microRNAs (miRNAs), long noncoding RNAs (lncRNAs), and circular RNAs (circRNAs) (Katsushima et al, 2014;Nakagawa et al, 2017;Wang et al, 2017;Wasik et al, 2017;Afonso et al, 2018;Wasik et al, 2020). We aimed to elucidate the dysregulated ncRNAs in PBC that contribute to the understanding of the pathogenesis of PBC by reviewing all currently published studies.…”
Section: Introductionmentioning
confidence: 99%